2022
DOI: 10.1002/adfm.202201535
|View full text |Cite
|
Sign up to set email alerts
|

New Structural Insights into Densely Assembled Reduced Graphene Oxide Membranes

Abstract: Densely assembled graphene‐based membranes have attracted substantial interest for their widespread applications, such as compact capacitive energy storage, ion/molecular separation, gas barrier films, and flexible electronics. However, the multiscale structure of densely packed graphene membranes remains ambiguously understood. This article combines X‐ray and light scattering techniques as well as dynamic electrosorption analysis to uncover the stacking structure of the densely stacked reduced graphene oxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 65 publications
1
19
0
Order By: Relevance
“…To evaluate the occupation number of large voids to the total pores of the membranes, we estimated the ratio between the slit number of large voids and the total slit number of the rGO membranes ( n voids / n total ) and found that it is <1.1% (Figure S7c) (see Methods for more details). Such a small percentage suggests that the contribution of the large voids to the total pore structures can be nearly neglected in the HI-reduced GO membranes compared to that in N 2 H 4 -reduced rGO membranes we recently reported, where a much higher content of such voids with a wider range of size distributions (30 ∼ 200 nm) exists . Unlike N 2 H 4 -rGO, the reaction in HI-rGO membranes neither leads to the loss of carbon atoms nor introduces the gaseous phase to the membrane, and it is thus expected to eventually contribute to the compact stacking of rGO nanosheets …”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…To evaluate the occupation number of large voids to the total pores of the membranes, we estimated the ratio between the slit number of large voids and the total slit number of the rGO membranes ( n voids / n total ) and found that it is <1.1% (Figure S7c) (see Methods for more details). Such a small percentage suggests that the contribution of the large voids to the total pore structures can be nearly neglected in the HI-reduced GO membranes compared to that in N 2 H 4 -reduced rGO membranes we recently reported, where a much higher content of such voids with a wider range of size distributions (30 ∼ 200 nm) exists . Unlike N 2 H 4 -rGO, the reaction in HI-rGO membranes neither leads to the loss of carbon atoms nor introduces the gaseous phase to the membrane, and it is thus expected to eventually contribute to the compact stacking of rGO nanosheets …”
Section: Resultsmentioning
confidence: 83%
“…42 A weak hump is observed in the low-q region (0.002 Å −1 to 0.1 Å −1 ) of the SAXS scattering curve (Figure 2b), indicating the existence of a group of large slit-like pores (i.e., voids) with a characteristic dimension (d void = 2π/q max ) at tens of nanometers. According to the structural model of rGO membranes established previously, 27 these slit-like voids are likely attributed to the gaps between the lamellae (an intermediate structure composed of stacked nanosheets). Specifically, the d void first increases from 32 nm (rGO-20-1h) to 73 nm (rGO-20-28h) and then decreases to 13 nm (rGO-20-99h) (Figure S7a,b).…”
Section: Resultsmentioning
confidence: 99%
“…Besides, the hierarchical structure of the graphene films can be fine‐tuned by using salt concentration to modulate their colloidal interactions to offer an exceptional volumetric capacitance in aqueous electrolytes. [ 116 ] Further, as mentioned above, we reported the first case of a dense yet porous carbon assembled with graphenes by simple evaporation, which has a density close to artificial graphite and pore structure similar to activated carbons, showing ultra‐high specific volumetric capacity in aqueous SCs. [ 11 ] Nevertheless, the relatively small pores are not suitable for the fast diffusion of ionic liquid electrolytes which can withstand the high voltage.…”
Section: Graphene Assembly For Compact Energy Storagementioning
confidence: 79%
“…[13][14][15][16][17][18] GO nanosheets are layered structures that operate as nanochannels for selective separation of water organic molecules. 15,[19][20][21][22][23][24][25][26] Due to tortuous pathways, GO membranes often show low permeation flux. [27][28][29] One suitable approach to enhance the flux is to widen the interlayer distance by adding intermittent materials, such as zeolite imidazole frameworks, 30 metalorganic frameworks, 31,32 TiO 2 , 33,34 carbon nanotubes, 35 and other functional materials.…”
Section: Introductionmentioning
confidence: 99%